Factors Affecting Productivity in Sudan During the Period (1970-2019) - Professor/ Khalafallah Ahmed Mohamed Arabi; Professor/ Salah Mohamed Ibrahim Ahmed; Ms. Mawada Mustafa Yousef (White Nile Journal for Studies and Research, 2026)
The study aimed to identify the factors affecting productivity in Sudan and analyze the nature of this relationship. The study assumed that human capital, labor growth, the general price level, and previous productivity have a direct impact on overall productivity. Data has been gathered from the Penn World Tables. We estimated three models: OLS, GMM single equation, and GMM system of equations. The study concluded that there is a positive relationship between labor growth and productivity, indicating a labor-intensive workforce in Sudan similar to other developing countries. The study recommended that there should be a focus on sustainable investment in education and training and the adoption of operational policies that ensure a balance between the growth of workers and the development of their efficiency for the continuity of productivity